Analisis Faktor Penentu Gagal Bayar Konsumen Pada Fifgroup Cabang Timika - Stepanus Sandy; Dinda Irfandi (Journal of Financial and Tax, 2022)
This study aims to determine the determinants of consumer defaults at the Timika Branch of Fifgroup. The method used in this study is a descriptive method to draw a series of factors that are formed to determine consumer defaults at the Timika Branch of Fifgroup. The data collection techniques used by researchers are observation, questionnaires and documentation, the analysis used by researchers is factor analysis. The results showed that there were two factors formed, namely the first factor was external factors as a determinant of consumer defaults in the timika branch of the fifgroup, namely the decline in economic activity and the high interest rates on loans utilizing an unhealthy competition climate by debtors of debtor business failure with the factor of disaster that occurred to debtors, the second factor was internal factors, namely poor faith from officers, weak credit administration and supervision system To overcome the default, Fifgroup Timika Branch should pay more attention specifically to external factors that result in a high risk of default which is the most dominant factor resulting in the level of default risk at Fifgroup Timika Branch. To minimize the occurrence of defaults on internal factors, you should pay more attention to the implementation of the credit process according to the SOP, provide anti-fraud training, improve human resources as a whole.